Guidelines for Examining Phonics & Word Recognition Programs. 2000 Edition. Texas Reading Initiative - Texas Education Agency, Austin; Texas Education Agency, Austin ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
To enable all children to learn to read with confidence and fluency, beginning reading instruction programs must offer balanced instruction that provides children with a variety of experiences. A full discussion of all the dimensions of a balanced program of beginning reading instruction is beyond the scope of this booklet. Rather, this booklet focuses on instruction in phonics and word recognition programs. The booklet aims to provide teachers with various guidelines to use to evaluate phonics and word recognition programs to determine if they reflect sound, research-based and classroom-tested instructional practices. The guidelines in the booklet can be used to evaluate the instruction found in both basal reading programs and supplemental programs. Part 1 of the booklet--The Content of Phonics and Word Recognition Instruction--provides information about the content of effective phonics and word recognition instruction, along with various guidelines for program evaluation and examination. Part 2--Reading Aloud and Independent Wide Reading--discusses reading aloud and independent reading as areas which receive attention because they contribute directly to children's ability to comprehend what they read, and are central to effective reading instruction. Part 3--Program Evaluation Checklists--contains checklists that may be useful to teachers as they examine the phonics and word recognition instruction found in either basal reading programs or supplemental programs. (Contains 15 references.) (NKA)
Availability: Publications Distribution Office, Texas Education Agency, P.O. Box 13817, Austin, TX 78711-3817.
Practitioners.
Teachers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Beginning Reading; Check Lists; Guidelines; Phonics; Primary Education; Program Evaluation; Reading Aloud to Others; Reading Fluency; Reading Instruction; Reading Programs; Word Recognition; Balanced Reading Instruction; Guides, Classroom -- Teacher; Guides, Non-Classroom.